1998
DOI: 10.1111/j.1442-9071.1998.tb01374.x
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of vasoactive properties of human retinal arteries after cryopreservation

Abstract: The response to constrictive (endothelin-I) and vasodilatory agents (nimodipine and betaxolol) was comparable with that in fresh pig vessels. It is now possible to obtain multiple segments of retinal artery from a single donor eye and to preserve them for detailed pharmacological assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In the present study we investigate the vasoactive properties of VEGF in an isolated perfused porcine retinal arteriole preparation. Porcine retinal arteries have been shown to exhibit similar vasoactive properties to human retinal arteries with a range of vasoactive agents [15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…In the present study we investigate the vasoactive properties of VEGF in an isolated perfused porcine retinal arteriole preparation. Porcine retinal arteries have been shown to exhibit similar vasoactive properties to human retinal arteries with a range of vasoactive agents [15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…The vasoactive effects of sodium fluorescein seen in the current study are therefore observed with sodium fluorescein levels considerably lower than that expected in fluorescein angiography. As we have previously demonstrated comparable vasoactive effects of other agents in pig and human vessels, 16,17 it may be reasonable to expect sodium fluorescein to have contractile effects on human vessels. If this is the case, then reducing illumination level may limit any vasoconstrictive effects of sodium fluorescein when used in routine ophthalmic examinations.…”
Section: Discussionmentioning
confidence: 92%